Knowledge and Practices Related to Added Salt in Meals by Food Handlers - Gonçalves,Carla (2014)
Objectives: To assess the knowledge and concerns about salt intake and added salt in meals, and to identify difficulties and proneness for a reduction of added salt in foods. Methodology: The present study was based on a questionnaire sent by mail to a randomly selected sample of 100 business units from a catering industry, so that food handlers filled out and returned the questionnaires through the mail. The return rate was 70%, and 68 subjects were considered after the rejection of 2 questionnaires. Results: The majority of the subjects (80.3%) recognized the maximum advised level of salt intake and 70.6% agreed with reducing the added salt to meals. The major difficulty for reducing the salt content of the meals was the consumer’s opinion (mentioned by 79.4%). Soups and salads were identified as major candidates to salt reduction, by 36.4% and 18.2% of the participants, respectively. Conclusions: Most of food handlers were aware about the recommended salt intake values, and are open to salt reduction strategies in food preparation.